Conciencia fonológica según género en niños de 5 años de una institución educativa del distrito Callao - Pacheco Cerván, Libia (2012)
The research was aimed to compare the performance of phonological awareness by gender in children 5 years of a state educational institution Initial Callao district. The research was descriptive, with a comparative descriptive design. The available sample consisted 80 students, who were administered the Test of metalinguistic skills (THM) Gomez, Valero, Buades and Perez (1995) adapted by Panca (2000). When processing the results found that most of the students in the sample were at the advanced level. The analysis of the scores showed that in most subs test administered to children no significant differences in the use of phonological awareness.